Optimizing Creative Thinking: STEAM-PjBL in Yogyakarta's Batik Science e-Book with Kawung Motif for Students - Setianingrum, Dwi Agnes; Jumadi, Jumadi (KnE Social Sciences, 2024)
Batik tulis is an Indonesian cultural heritage with a rich meaning and philosophical value. Although batik is often taught in the arts, the process of batik can also be integrated into science learning. This research aims to analyze: (1) the feasibility of science e-book containing local wisdom of batik tulis Yogyakarta kawung motif based on STEAM-PjBL, (2) the practicality of science e-book containing local wisdom of batik tulis Yogyakarta kawung motif based on STEAM-PjBL, and (3) the effectiveness of science e-book containing local wisdom of batik tulis Yogyakarta kawung motif based on STEAM-PjBL in improving students’ creative thinking skills. The study uses the Thiagarajan 4D development model (Four-D Model), consisting of four stages, namely the define, design, develop, and disseminate. The results showed that: (1) The science e-book containing local wisdom of batik tulis Yogyakarta kawung motif based on STEAM-PjBL was feasible to use, judging from the results of the material validator, 79.50 (very good), and the results of the teaching material validator, 33.00 (very good). (2) Student response was 3.28 (very good). (3) Results of the N-Gain and Effect Size analysis of the science e-book containing local wisdom of batik tulis Yogyakarta kawung motif based on STEAM-PjBL was quite effective in improving students’ creative thinking skills (N-Gain 0.56 [medium], Effect Size 0.9 [high]). Keywords: creative thinking skill, development research, science e-book, STEAM-PjBL